Monogamy in the Burrowing Shrimp Axianassa australis Rodrigues & Shimizu, 1992 (Decapoda, Gebiidea, Axianassidae) - Hernáez, Patricio; Mugnai, Riccardo; Souza-Filho, Jesser F.; Pinheiro, Marcelo Antonio Amaro [UNESP] (University of Chicago Press, 2022)
Our knowledge of the mating systems in burrowing shrimps (infraorders Axiidea and Gebiidea) is still rather limited. Here we describe the burrow use pattern, sex ratio, and sexual dimorphism of the burrowing shrimp Axianassa australis to test for monogamy, considering that monogamous species live in heterosexual pairs and exhibit a low degree of sexual dimorphism. To this end, a total of 226 individuals of A. australis were collected from the northeast region of Brazil. Our results showed that A. australis inhabited its burrows mainly as pairs, most of which were male-female pairs. In agreement with the expectations, specimens of A. australis were found dwelling as heterosexual pairs more frequently than expected by chance alone. The presence of ovigerous females was associated with the burrow occupation; that is, brooding females were more frequently observed in male-female combinations than solitarily. Also supporting theoretical considerations, we did not observe sexual dimorphism in body size between males and females of the population and the different categories of the burrow occupation. Conversely, sexual dimorphism in cheliped size was evident in the population, with larger chelipeds in males than in females. This observation agrees with that re- ported for most burrowing shrimps in which male-male competition is the main evolutionary force of sexual selection. The observations above favor the hypothesis that A. australis is primarily monogamous, with a small fraction of the males moderately promiscuous.